An analysis of lethal and sublethal interactions among type I and type II pyrethroid pesticide mixtures using standard Hyalella azteca water column toxicity tests. (21st June 2016) - Hoffmann, Krista Callinan; Deanovic, Linda; Werner, Inge; Stillway, Marie; Fong, Stephanie; Teh, Swee
Abstract: A novel 2‐tiered analytical approach was used to characterize and quantify interactions between type I and type II pyrethroids in Hyalella azteca using standardized water column toxicity tests. Bifenthrin, permethrin, cyfluthrin, and lambda‐cyhalothrin were tested in all possible binary combinations across 6 experiments. All mixtures were analyzed for 4‐d lethality, and 2 of the 6 mixtures (permethrin–bifenthrin and permethrin–cyfluthrin) were tested for subchronic 10‐d lethality and sublethal effects on swimming motility and growth. Mixtures were initially analyzed for interactions using regression analyses, and subsequently compared with the additive models of concentration addition and independent action to further characterize mixture responses. Negative interactions (antagonistic) were significant in 2 of the 6 mixtures tested, including cyfluthrin–bifenthrin and cyfluthrin–permethrin, but only on the acute 4‐d lethality endpoint. In both cases mixture responses fell between the additive models of concentration addition and independent action. All other mixtures were additive across 4‐d lethality, and bifenthrin–permethrin and cyfluthrin–permethrin were also additive in terms of subchronic 10‐d lethality and sublethal responses. Environ Toxicol Chem 2016;35:2542–2549. © 2016 SETAC